Implementation of uMusic project - Khoo, Christopher Zhan Peng. (2011)
Web 3.0 is believed to be using intelligence agents to automate the process of sourcing and updating information. The motivation of this project is to recommend music to users by delivering a hassle-free music system that is able to automate the process of maintaining and refreshing playlists. It too focuses on cloud music to give user for more stability and accessibility.